Comments on 'Differentiator application in altitude control for an indoor blimp robot'. Issue 5 (3rd May 2020) - Mboup, M.; Join, C.; Fliess, M.; Wang, Y.; Zheng, G.; Efimov, D.; Perruquetti, W.
ABSTRACT: Comparison of several types of differentiation algorithms has been performed in the paper Wang, Zheng, Efimov, and Perruquetti [(2018). Differentiator application in altitude control for an indoor blimp robot. International Journal of Control, 1–10. Retrieved from https://doi.org/10.1080/00207179.2018.1441549 ] with application to a robotic blimp altitude control. Unfortunately, one of the differentiation methods, the algebraic differentiator, has not been applied properly. The clarifications and the new comparison results are given in this note.